Strategi Kebijakan untuk Mendukung Stabilitas Harga Bawang Merah - Adetya, Aulia; Sidqi, Ilham Fajar (Policy Brief Pertanian, Kelautan, dan Biosains Tropika, 2024)
Shallots are one of the main agricultural crops that have the potential to significantly contribute to horticultural production and influence inflation. Shallots hold high economic value, making an important contribution to Gross Domestic Product (GDP). Additionally, they serve as a source of income for farmers and have the potential to earn foreign exchange. However, the distribution of shallots faces many challenges, including the imbalance between production centers and consumer areas, as well as the prolonged involvement of intermediaries in the supply chain. To ensure price stability for shallots, comprehensive and targeted policy interventions are needed. One of the primary recommendations is to strengthen the price fluctuation control system. The government should develop a price stabilization mechanism through market intervention instruments, such as setting reference prices and conducting market operations when shallot prices spike. Protecting local farmers is also a priority in maintaining shallot price stability. By implementing these policies, better stability in shallot prices can be achieved.